EFFECT OF HEATING RATE ON THE PROPERTIES OF BISMUTH-BASED SUPERCONDUCTING MATERIALS - Mehmood , Rashid; Iqbal, Muhammad Javed (Journal of Research (Science), 2007)
Bismuth based superconducting materials having a general formula Bi2-x Pb0.4Sr2Ca2 Cu3Oy (where x = 0.1, 0.2, 0.3 and 0.4) were synthesized by the simple solid-state reaction method. Each of the samples was initially calcined at three temperatures of 790oC at different heating rates of 2, 5, 10, 14 and 20 oC min-1 for 24h. The sample pellets were sintered in air at three different temperatures of 835oC for 48 h at the heating rates given above. The lattice parameters (a, b and c) and unit cell volume, Vcell, of the samples were calculated by X-ray diffraction (XRD). The dc electrical resistivity and ac magnetic susceptibility measurements show that the sample with the value of x = 0.3, sintered at 835oC, at a heating rate of 14oC.min-1 has the highest percentage of the high-Tc (2223) phase, the highest value of Tc(0) =106 K and the lowest room temperature resistivity value.